(untitled) - Black, Christopher (New York, 2017)
Dramatically raise your SAT score with this cross-platform prep course filled with practice tests, powerful analytics, test-taking tips, and more! Includes 8 full-length practice tests, 4 in the book + 4 interactive tests online or the app Planning to take the SAT? We’ve put all our proven expertise into McGraw-Hill Education SAT to make sure you’re ready for this difficult exam. With this book, you’ll get essential skill-building techniques and strategies developed by professional SAT instructors who have helped thousands of students just like you to succeed on this important test. You’ll get online help, 4 full-length practice tests in the book and 4 more interactive tests online and/or on the app, hundreds of practice problems, time-saving techniques for each question type, and all the essential facts about the current exam. With McGraw-Hill Education SAT, we’ll guide you step-by-step through your preparation program – and give you the tools you need to succeed!
Keywords: SAT (Educational test),SAT (Kiểm tra giáo dục)